Future carbon fund delivering co benefits for sustainable development. (Asian Development Bank, 2017)
Asia and the Pacific is home to more than 60% of the worlds population and 62% of the global economic output. But the region still faces enormous development challenges and with economic growth, it has become a major source of greenhouse gas (GHG) emissions. This has exposed Asia and the Pacific to the impacts of climate change, threatening to undo the development gains from economic prosperity over the past decades. This report reflects how Clean Development Mechanism projects supported by the Future Carbon Fund not only reduce GHG emissions but deliver social, environmental, and economic co benefits contributing to sustainable development in the region. This report also presents qualitative and quantitative analysis of these co benefits.